2015
DOI: 10.1149/06604.0305ecst
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Temperature of Al2O3 Atomic Layer Deposition Using Accurate Process Gasses Supply System

Abstract: Al2O3 is one of the most expectancy high-k materials for high density on-chip metal-insulator-metal (MIM) capacitors as well as gate insulator for composed semiconductor power devices. In this paper, using the developed atomic layer deposition (ALD) process equipment with multiple oxidation methods and accurate process gas supply system adapted to high temperature usage, the impact of the process temperature on the electrical characteristics of Al2O3 films was investigated. It was found that the substrate mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…To define MIM area, SiO 2 films were deposited by atmospheric pressure chemical vapor deposition with SiH 4 and O 2 mixed gases at 400°C and the wet etching with the buffered HF was carried out. In both case, after the native oxide on active regions was removed by diluted HF (0.5%), Al 2 O 3 films were deposited by ALD (12,13). Here, ALD was carried out as follows.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To define MIM area, SiO 2 films were deposited by atmospheric pressure chemical vapor deposition with SiH 4 and O 2 mixed gases at 400°C and the wet etching with the buffered HF was carried out. In both case, after the native oxide on active regions was removed by diluted HF (0.5%), Al 2 O 3 films were deposited by ALD (12,13). Here, ALD was carried out as follows.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the radical oxidation in ALD, it is suggested by XPS evaluation that the oxidizing reaction is occurred at the Al 2 O 3 /Si interface during ALD and Al x Si y O z layer is formed at the interface (12). In the former study, H 2 O oxidation at stage temperature of 75 °C was shown to be effective because oxidizing Si does not occur (12). However the oxidation ability of H 2 O is relatively low at such low temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the temperature of ALD is one of the important parameters in relation to the chemical reaction and the dissolution of supply gasses, such as trimethylaluminum (TMA) for Al 2 O 3 . A recent study reported that an excessive high temperature may cause the spontaneous decomposition of TMA and the substrate material must not be oxidized during the oxidation process [7]. In the former study, H 2 O oxidation at stage temperature of 75 °C was shown to be effective [7].…”
Section: Introductionmentioning
confidence: 93%
“…A recent study reported that an excessive high temperature may cause the spontaneous decomposition of TMA and the substrate material must not be oxidized during the oxidation process [7]. In the former study, H 2 O oxidation at stage temperature of 75 °C was shown to be effective [7]. However, the oxidation ability of H 2 O becomes low at such low temperature.…”
Section: Introductionmentioning
confidence: 96%